GAPDH: the missing link between glycolysis and mitochondrial oxidative phosphorylation?. (23rd September 2013) - Ramzan, Rabia; Weber, Petra; Linne, Uwe; Vogt, Sebastian
Abstract : The main function of glycolysis and oxidative phosphorylation is to produce cellular energy in the form of ATP. In the present paper we propose a link between both of these energy-regulatory processes in the form of GAPDH (glyceraldehyde-3-phosphate dehydrogenase) and CytOx (cytochrome c oxidase). GAPDH is the sixth enzyme of glycolysis, whereas CytOx is the fourth complex of the mitochondrial oxidative phosphorylation system. In MS analysis, GAPDH was found to be associated with a BN-PAGE (blue native PAGE)-isolated complex of CytOx from bovine heart tissue homogenates. Both GAPDH and CytOx are highly regulated under normal energy metabolic conditions, but both of these enzymes are highly deregulated in the presence of oxidative stress. The interaction of GAPDH with CytOx could be the point of interest as it has already been shown that GAPDH protein damage results in a marked decrease in cellular ATP levels. On the other hand, decreasing the ATP/ADP ratio may ultimately result in switching off the allosteric ATP inhibition of CytOx leading to increased ROS (reactive oxygen species), cytochrome c release and apoptosis. Moreover, we have previously reported that allosteric ATP inhibition of CytOx is responsible for keeping the membrane potential at low healthy values, thus avoiding the production of ROS and this allosteric ATP inhibition is switched on at a high ATP/ADP ratio. So, in the present paper, we propose a scheme that could prove to be a link between these two enzymes and their role in the prevalence of diseases.